Pengaruh Penambahan Natrium Hipokhlorit Pada Proses Pembekuan Air Baku Es Batu Terhadap Penurunan Jumlah E coli - Dadang Tri Wibowo; Lucky Herawati; Narto Narto (Poltekkes Kemenkes Yogyakarta, 2010)
Eschrerichia coli is used as a water contamination indicator which giving infor-mation about the possibility of water contamination by pathogenic microorga-nisms. For economic and practical reasons, the raw water used as the source of ice cube making sometimes are not boiled nor disinfected, therefore it is not safe to be consumed. To provide information on the applicability of natrium hypochloride (NaOCl )as an alternative disinfectant, this research is aimed to under-stand the decrease of MPN E. coli by using this chemical compound. This research is an experimental one with pre test-post test with control design. Data obtained from fifteen raw water sample is analysed descriptively as well as analytically by using paired sample t-test at 95% confidence level to com-pare the average differences between ice cube added by NaOCl and those which are not. It is concluded that the addition of NaOCl can reduce the MPN E. coli significantly (p<0,001), and the subsequent organoleptic test on the taste and odour of the two types of ice cube, shows that the disinfected ones is still acceptable to consumers .